Uncertainty and employment dynamics in the euro area and the US - Aleksei Netésunajev; Katharina Glass (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
In this paper we investigate transmission and spillovers of local and foreign economic policy uncertainty shocks to unemployment in two largest economic regions in the world - the United States (US) and the Euro area (EA). For this purpose we deploy Bayesian Markov-switching structural vector autoregressive (MS-SVAR) model identified via heteroskedasticity. In addition to local effects we find foreign uncertainty shocks influence the Euro area but not the US unemployment. Moreover we document weaker spillovers of both local and foreign uncertainty shocks in the more volatile times.
Keywords: D80; C32; C11; E24; 330; economic policy uncertainty; EPU index; unemployment; Markov-switching; structural vector autoregression; identification via heteroskedasticity; Bayesian inference